Expectations and the structure of share prices - Cragg, J. G.; Malkiel, Burton Gordon (Chicago : University of Chicago Press, 1982)
It serves to increase considerably our knowledge of the workings of the stock market.
Includes index.
Bibliography: p. 167-169.
ucj, 15/01/2019
Loans
Keywords: Stocks; Corporate profits; Capital assets pricing model; Mathematical models